2022
DOI: 10.3389/fpubh.2022.939758
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning model for depression based on heavy metals among aging people: A study with National Health and Nutrition Examination Survey 2017–2018

Abstract: ObjectiveTo explore the association between depression and blood metal elements, we conducted this machine learning model fitting research.MethodsDatasets from the National Health and Nutrition Examination Survey (NHANES) in 2017–2018 were downloaded (https://www.cdc.gov/nchs/nhanes). After screening, 3,247 aging samples with 10 different metals [lead (Pb), mercury (Hg), cadmium (Cd), manganese (Mn), selenium (Se), chromium (Cr), cobalt (Co), inorganic mercury (InHg), methylmercury (MeHg) and ethyl mercury (Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
(33 reference statements)
0
17
1
Order By: Relevance
“…At present, there is no definite conclusion on the correlation between the LTI angle and the patellar cartilage injury. Stefanik and other researchers have asserted that the LTI angle is significantly related to the patellar cartilage injury, but this is just opposite to the conclusion of previous reports (29)(30)(31)(32)(33)(34). In this study, the LTI angle of the control group was significantly greater than that of the CP group, which was consistent with Stefanik's conclusion.…”
Section: Discussioncontrasting
confidence: 59%
“…At present, there is no definite conclusion on the correlation between the LTI angle and the patellar cartilage injury. Stefanik and other researchers have asserted that the LTI angle is significantly related to the patellar cartilage injury, but this is just opposite to the conclusion of previous reports (29)(30)(31)(32)(33)(34). In this study, the LTI angle of the control group was significantly greater than that of the CP group, which was consistent with Stefanik's conclusion.…”
Section: Discussioncontrasting
confidence: 59%
“…The increased activity of the amygdala also activates the HPA axis, stimulates the release of corticotropin-releasing hormone, induces skin inflammation through mast cell degranulation, and enhances vascular permeability. Stress could also activate dendritic cells in the skin, leading to the release of neurotransmitters and catecholamines through nerve endings in the skin, aggravating skin diseases (35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing blood sugar, empagliflozin can also improve islet function and affect blood lipids. Weight loss and blood pressure reduction play a role in multiple organ protection, including in the cardiovascular system (28) and the kidneys (29)(30)(31)(32), which play a role in delaying the occurrence and development of T2DM complications. Some studies (30)(31)(32) have shown that SGLT-2 inhibitors have a lower incidence of major cardiovascular adverse events, heart failure, and mortality in patients with T2DM during clinical use.…”
Section: I a B E T E S I S A C H R O N I C D I S E A S E C H A R A C ...mentioning
confidence: 99%
“…Weight loss and blood pressure reduction play a role in multiple organ protection, including in the cardiovascular system (28) and the kidneys (29)(30)(31)(32), which play a role in delaying the occurrence and development of T2DM complications. Some studies (30)(31)(32) have shown that SGLT-2 inhibitors have a lower incidence of major cardiovascular adverse events, heart failure, and mortality in patients with T2DM during clinical use. Due to these significant effects, SGLT-2 inhibitors are also recommended as first-line oral hypoglycemic agents for T2DM complicated with coronary heart disease (30).…”
Section: I a B E T E S I S A C H R O N I C D I S E A S E C H A R A C ...mentioning
confidence: 99%
See 1 more Smart Citation